Neorhynchoplax yaeyamaensis, a new false spider crab (Decapoda: Brachyura: Hymenosomatidae) from the Yaeyama Group, the Ryukyu Islands, Japan - Naruse, Tohru; Shokita, Shigemitsu; Kawahara, Takeshi (Zootaxa, 2005)
A new false spider crab, Neorhynchoplax yaeyamaensis (Decapoda: Brachyura: Hymenosomatidae) is described from the Yaeyama Group, the Ryukyu Islands, Japan. Neorhynchoplax yaeyamaensis is morphologically close to N. exigua and N. aspinifera, however, N. yaeyamaensis is easily differentiated from the latter two species by the dentition of the ambulatory dactyli, and the shapes of the carapace, male abdomen, and G1. Neorhynchoplax okinawaensis, also found in the Ryukyu Islands, differs from N. yaeyamaensis by the presence of a posterior lateral tooth, and the shape of the carapace, male abdomen, and G1.